Parameter estimation of three-phase linear induction motor by a DSP-based electric-drives system - Nicolás Toro García; Yeison Alberto Garcés Gómez; Fredy Edimer Hoyos Velasco (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This work describes a method to characterize a three-phase linear induction motor in order to determine the various parameters used in its per-phase equivalent circuit by a DSP-based electric-drives system. In LIM (Linear Induction Motor), the air gap is very large compared with the RIMs (Rotary Induction Motors). Further, the secondary part normally does not have slotted structure. It is just made of aluminum and steel plates. Therefore, the effective air gap is larger than the physical air gap. High air gap makes a larger leakage inductance. It leads to lower efficiency and lower power factor. DC resistance test will be done to determine the value of Rs. The primary Inductance Ls will be calculated by running the LIM at synchronous speed. The secondary parameters i.e. Llr and Rr′ will be calculated by blocked-mover test. The experiment for no load test is shown and include a DC motor coupled to the LIM under test. Two methods to calculate the secondary parameters are described.